UAVs for the Environmental Sciences Methods and Applications (Wissenschaftliche Buchgesellschaft (wbg), 2022)
This book gives an overview of the usage of UAVs in environmental sciences covering technical basics, data acquisition with different sensors, data processing schemes and illustrating various examples of application.